The Influence of Capital Adquacy Ratio and Non Performing Loan on Return On Asset - Elsa Thyovani; Gusganda Suria Manda (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
Bank performance can be measured using Return On Assets as a measuring tool for a company in achieving profitability in the form of assets owned by the company. This study aims to determine the effect of the ratio of capital adequacy and non-performing loans on return on assets. The population of this study are several banking companies listed on the IDX in the 3 year observation period (2017-2019). This study took samples taken using purposive sampling method. Based on the results of multiple linear regression analysis which shows that the capital adequacy ratio has a positive and significant effect on asset returns, meanwhile non-performing loans have a negative and insignificant effect on asset returns.